THE ROLE OF LEADERSHIP, TEAMWORK, AND BUSINESS PROCESS IN AFFECTING THE PERFOMANCE OF ACCOUNT MANAGER AT PT. TELKOM INDONESIA IN SELLING THE VPN PRODUCTS - Febryandoko, Febryandoko; Mei Nur Widigdo, Aslam (Dinasti Publisher, 2021)
This research has been purposed to discover and analyze the role of leadership, teamwork and business process on the achievement of account manager in selling the VPN products. These research methods used a quantitative approach by multiple linear regression analysis to examine the hypothesis. The research population and research sample were 85 respondents who work as Account Manager of the Manufacturing Segment, Service Business Division at PT. Telkom throughout Indonesia.The results showed if the leadership, teamwork and business process partially had a positive affect on the performance of the account manager in VPN sales. It also simultaneously affects the account manager's performance in VPN sales.